Discovery of a new species of Embolemus Westwood (Hymenoptera: Embolemidae) from New Caledonia - Contarini, Mario; Olmi, Massimo; Capradossi, Leonardo; Guglielmino, Adalgisa (Zootaxa, 2020)
Embolemus villemantae sp. nov. (Hymenoptera: Embolemidae) is described from New Caledonia. The key to the males of the Australasian species of Embolemus is modified to include the new species.